Global epidemiology of antimicrobial resistance in commensal Neisseria species: A systematic review - Thibaut Vanbaelen; Christophe Van Dijck; Jolein Laumen; Natalia Gonzalez; Irith De Baetselier; Sheeba S. Manoharan-Basil; Tessa De Block; Chris Kenyon (Elsevier, 2022)
Background: Commensal Neisseria species (spp). represent an important reservoir of antimicrobial resistance genes for pathogenic Neisseria spp. In this systematic review, we aimed to assess the antimicrobial susceptibility of commensal Neisseria spp. and how this has evolved over time. We also aimed to assess if commensal Neisseria spp. showed intrinsic resistance to four antimicrobials - penicillin, azithromycin, ceftriaxone and ciprofloxacin. Methods: Pubmed and Google Scholar were searched following the PRISMA guidelines. Articles reporting MICs of commensal Neisseria spp. were included according to inclusion/exclusion criteria, and the quality of the articles was assessed using a pre-designed tool. Individual and summary measures of penicillin, azithromycin, ceftriaxone and ciprofloxacin MICs were collected. Additional data was sought to perform a comparison between the MICs of pathogenic and commensal Neisseria spp. Results: A total of 15 studies met our criteria.We found no evidence of intrinsic AMR in commensal Neisseria spp. We did find evidence of an increasing trend in MICs of commensal Neisseria spp. over time for all antimicrobials assessed. These findings were similar in various countries. Eight additional studies were included to compare pathogenic and commensal Neisseria spp. Conclusion: The MICs of commensal Neisseria spp. appear to be increasing in multiple countries. Surveillance of MICs in commensals could be used as an early warning system for antimicrobial resistance emergence in pathogens. Our findings underline the need for antibiotic stewardship interventions, particularly in populations with high antimicrobial consumption.